Salt reduction behavior of adults in Anhui province in 2019: a cross-sectional survey of 3,378 participants - Xing, Xiu-Ya; Zhao, Yan; Sam, Napoleon Bellua; Xu, Jing-Qiao; Chen, Ye-Ji; Xu, Wei; Wang, Hua-Dong; Liu, Zhi-Rong; Pan, Hai-Feng (Frontiers in Public Health, 2023)
Objective: High-sodium diet is an important risk factor for hypertension in Chinese population, which can increase the risk of cardiovascular and cerebrovascular diseases. Although a large number of related studies have been carried out in Anhui province, clear, effective salt reduction interventions and policies that can be widely promoted have not yet been formed. This study sought to understand the prevalence and precise measures of salt reduction behavior, the variables affecting salt reduction behavior, and the reasons why salt reduction behavior was not practiced in Anhui Province, China. Methods: The total number of participants was 3,378. Using a multi-stage stratified cluster random sampling method, residents between the ages of 18 and 69 in 10 counties and districts were selected from March to October 2019. A survey questionnaire and physical measurements were given to each participant. The influencing factors of residents' salt reduction behavior holding were examined using a multi-factor unconditional logistic regression analysis. The Chi-square (χ 2 ) test was used to analyze the implementation of salt reduction behaviors among different age groups and genders, the factors influencing the implementation of salt reduction measures, and the reasons for not implementing salt reduction measures. Results: A history of hypertension was associated with salt reduction strategies (P=0.014). Patients with hypertension were more likely to adopt salt reduction behaviors than those without hypertension (OR=1.218, P=0.040). The influence of eating out on the adoption of saltreduction measures varied by age groups ( 2 =50.463, P<0.001) and gender ( 2 =81.348, P<0.001).In summary, residents of Anhui Province are not very knowledgeable about salt reduction. Age, gender, education level, hypertension, and marital status are the main determinants. Our findings have significant implications for policymakers who want to specify salt reduction strategies.